Provocation with adenosine 5′-monophosphate, but not methacholine, induces sputum eosinophilia - Van den berge, M.; Kerstjens, H. A. M.; De reus, D. M.; Koëter, G. H.; Kauffman, H. F.; Postma, D. S. (Clinical and experimental allergy, 2004)
Summary Introduction Bronchial hyper‐responsiveness is usually measured with direct stimuli such as methacholine (MCh) or histamine. Adenosine 5′‐monophosphate (AMP), which acts indirectly via the secondary release of mediators, is another stimulus to measure bronchial hyper‐responsiveness. Aim To investigate whether provocation with inhaled AMP itself initiates an inflammatory response resulting in an influx of eosinophils into the airway lumen. Methods We have included 21 non‐smoking atopic asthmatic subjects (mean FEV1 101% predicted, mean age 34 years). Each subject performed three sputum inductions on different days, at least seven days apart: one without previous provocation, one hour after PC20 methacholine, and one hour after PC20 AMP. Results After provocation with AMP, but not methacholine, the percentage of sputum eosinophils increased significantly (from 1.9±0.5% to 4.5±1% (P<0.01) and 1.9±0.5% (P=0.89)). No changes in the percentages of neutrophils, lymphocytes, macrophages, or bronchial epithelial cells were found. Conclusion A provocation test with AMP leads to an increased percentage of sputum eosinophils. This observation cannot be explained by a non‐specific response of the airways to a vigorous bronchoconstriction, since methacholine had no effect on inflammatory cells.